Study of The Bioactivity and Antioxidant Activity of Dried Fig Puree and Its Effect on The Shelf Life of Ice Cream - Ethafa, Esraa (University of Thi-Qar Journal of agricultural research, 2025)
Dried figs were mashed, to assess the DPPH radical scavenging capacity, at concentrations of 0, 5, 10, and 15 mg/ ml, comparison with 5 mg ml ascorbic acid. Ice cream was made and supplemented with dried fig puree, at four replacement ratios (0, 1, 3, and 6%) symbol by T0, T1, T2, and T3 respectively. Physical and sensory tests were performed after 0, 3, 7, and 10 days. The solubility of the dried fig puree extract ranged from 85.97-42.51%, pH value (6.33-5.06%), the acidity value (0.14-0.27%), the spread ability (15.11-11.26%), the solubility (35.25-26.32%), the taste (19.39-13.02%), the aroma (18.35-12.01%), and the overall acceptability (19.35-11.09%). The active compounds of the aqueous and alcoholic dried fig extracts were identified by GC-MS, using an Agilent Technologies 7890B GC system, the aqueous extract yielded 10.172, 16.119, and 26.3148% area percentages, respectively, for the compounds 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl-, 8-(2-Phenylethyl)-1-oxa-3,8-diazaspiro[4,5]decan-2-one, and methane-diethoxy, while the alcoholic extract yielded 6.931% area percentages, 11.002% area percentages, and 11.0542% area percentages, for the compounds Dimethyl 2,5-thiophenedicarboxylate, Dimethyl 2,51-Methyl-5-fluorouracil, and 1,3,5,7-Tetroxane. This indicates that adding dried plant extracts to ice cream, led to improved composition and physicochemical, biological, and sensory properties.